Dampak Just in Time (JIT) terhadap Kinerja Operasional : Literature Review - Wahyudi Nur Hidayat; Krisna Praditya; Sabikah Ulima Paw Waz; Galang Hanipan; Helmy Royaldi; Mukhtaruddin, Mukhtaruddin (Jurnal Riset Akuntansi, 2025)
In the face of increasingly intense business competition, improving operational performance has become a critical priority for companies. One widely adopted strategy to achieve efficiency is the Just In Time (JIT) system. This study applies a Systematic Literature Review (SLR) method to analyze the impact of JIT implementation on companies' operational performance. The findings reveal that JIT significantly contributes to reducing storage costs, enhancing production efficiency, speeding up distribution processes, and increasing operational flexibility and customer satisfaction. However, the success of JIT implementation largely depends on effective coordination with suppliers, technological readiness, and the competence of human resources.